The road and belt initiative in Malaysia : challenges and recommendations - Ku, Boon Dar; Tan, Chee Seng (Penerbit Universiti Kebangsaan Malaysia, 2021)
In recent years, China has expanded its relations with other nations through the Belt and Road Initiative. This initiative was formally introduced after it was launched in 2013 by President Xi Jinping. It comprises two components, namely, the Silk Road Economic Belt and the 21st Century Maritime Silk Road Initiative, both of which aim to stimulate the acceleration of economic growth in Asia, Africa and Europe. This research attempts to provide a detailed review of the execution of this initiative through empirical studies based on qualitative analysis, which are closely related to BRI implementation in Malaysia. The focus of this research, however, is not limited to studying the viewpoints of leaders and scholars on the initiative; rather, it will also attempt to discuss theBRI’s progress and the obstacles encountered to date from the political aspects of both China and Malaysia. By identifying the potential challenges to come, this research will prove to be significant, as it proposes some comprehensive measures to address and forestall any setbacks that may arise, which may affect the implementation of the BRI between the two nations.